ISU DALAM PRODUK KEUANGAN SYARIAH : SUKUK - Eka Sri Wahyuni (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2018)
: Sukuk is a syariah effect in the form of certificates or proof of ownership of equal value and represents an undivided or indivisible portion of the ownership of certain tangible assets, the value of benefits, and services for a particular project asset or activity. Types of sukuk many kinds in accordance with the contract used. However, in the financial services authority report there are only two sukuk namely mudharabah and ijara.The development of sukuk globally has increased every year. With the rapid development of sukuk is clearly a good opportunity for economic progress, especially Indonesia and the most important challenge is the role of standard regulatory bodies in particular will be critical in facing the problem of sukuk in the secondary market and primary market through the harmonization of practices and guidelines and documentation standards for the structure of a particular sukuk.